Poverty, agrarian structure and political economy in India - Bardhan, Pranab (New Delhi, 2003)
This is a collection of Bardhan's classic writings covering a range of his interests in the Indian economy, society and polity. The essays, written over a span of over three decades, vary from broad-brush think-pieces to detailed field survey results and econometric exercises.
Keywords: Poverty